Penerapan Model Pembelajaran Talking Stick Untuk Meningkatkan Hasil Belajar Matematika Siswa pada Materi Aritmetika Sosial - Nurfaida Baid; Evi Hulukati; Kartin Usman; Siti Zakiyah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This study aims to improve students' mathematics learning outcomes on social arithmetic topics by applying the Talking Stick learning model. This type of research includes the type of classroom action research. The study involved 23 students from one of the junior high schools in Bone Bolango Regency as research subjects. The technique used in data collection is observation and tests. The technique used in data collection is observation and tests. The data analysis techniques in this study were teacher observation data analysis, student observation data analysis, and test analysis of learning outcomes. The research procedures are action planning, implementation, observation, and reflection. This research was conducted in stages with cycles, namely cycles I and II. The results showed that the percentage of students who completed mathematics learning outcomes was 52.20% in the first cycle and 82.60% in the second cycle. Thus, there is an increase in students' mathematics learning outcomes by 30.40%. Based on the study results, it can be concluded that student learning outcomes on social arithmetic material have increased after the implementation of the Talking Stick learning model with two cycles of learning stages.